Mathematics Anxiety Level in Tenth-Grade Students on Quadratic Function Topic at Orphanage - Nada Nabilah; Halini Halini; Silvia Sayu (Universitas Tanjungpura, 2023)
This study aims to determine and describe studentsâ€™ mathematics anxiety levels on the quadratic function in tenth grade in Al-Amien orphanage, Pontianak. This research method used was descriptive in the form of a survey. The number of subjects in this research was six students of tenth grade at orphanage. Based on the questionnaire on anxiety level, it was found there are two levels of anxiety experienced by the students, namely moderate mathematics anxiety, and severe mathematics anxiety. Three students experience each a level of anxiety. In addition to administering questionnaires, students were given mathematics tests and interview questions. From the result of data processing carried out, three students have moderate levels of anxiety and three students who have severe anxiety levels.Â Keywords:Â Mathematics Anxiety, Quadratic Functions, Descriptive